The boy who saved my life : walking into the light with my autistic grandson - Martin, Earle P., 1933- (Houston, Tex. : Bright Sky Press, 2011)
At age two and a half, Charlie stopped speaking. He wouldn't answer his family. He wouldn't look at them. They were frightened, but they were determined to fight for him. "The Boy Who Saved My Life" is a story of love and redemption that will inspire the reader to reach out and experience an incredible, life-changing relationship with a special person. For the author, that special person is his grandson Charlie, who is autistic. Earle Martin knew he must open up to Charlie in a way he had never done with anyone. He had to come out of his dark world to meet Charlie in his world. If he was going to help Charlie, they had to walk hand in hand into the light of a better world. Martin hopes to introduce the reader to special-needs individuals in a way that will encourage involvement with them and affect positive life changes through the inspiration of the special needs community.
Includes bibliographical references and index.
Keywords: Martin, Earle P., -- 1933-; Martin, Charlie; Autism in children -- United States -- Biography; Autistic children -- Family relationships; Grandfathers